COVID-19 and Food Safety FAQ: Shopping and Handling Groceries: FSHN20-26/FS367, 4/2020 - Danyluk, Michelle; Seymour, Natalie; Yavelak, Mary; Christian, Candice; Chapman, Ben (EDIS, 2020)
This new one-page flyer answers food safety questions about preventing COVID-19 transmission when grocery shopping and handling groceries. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension) and published by the UF/IFAS Food Science and Human Nutrition Department. Revised April 21, 2020: Changes were made relating to physical distancing, mask usage and monitoring employee health when exposed to the virus. FSHN20-26/FS367: COVID-19 and Food Safety FAQ: Shopping and Handling Groceries (ufl.edu)